Folic acid delays development of atherosclerosis in low‐density lipoprotein receptor‐deficient mice. Issue 6 (23rd March 2018) - Pan, Sunlei; Liu, Huahua; Gao, Feidan; Luo, Hangqi; Lin, Hui; Meng, Liping; Jiang, Chengjian; Guo, Yan; Chi, Jufang; Guo, Hangyuan
Abstract: Many studies support the cardioprotective effects of folic acid (FA). We aimed to evaluate the utility of FA supplementation in preventing the development of atherosclerotic in low‐density lipoprotein receptor‐deficient (LDLR−/−) mice and to elucidate the molecular processes underlying this effect. LDLR−/− mice were randomly distributed into four groups: control group, HF group, HF + FA group and the HF + RAPA group. vascular smooth muscle cells (VSMCs) were divided into the following four groups: control group, PDGF group, PDGF + FA group and PDGF + FA + RAPA group. Blood lipid levels, oxidative stress and inflammatory cytokines were measured. Atherosclerosis severity was evaluated with oil red O staining. Haematoxylin and eosin (H&E) staining was used to assess atherosclerosis progression. Immunohistochemical staining was performed with antismooth muscle α‐actin (α‐SMA) antibodies and anti‐osteopontin (OPN) antibodies that demonstrate VSMC dedifferentiation. The protein expression of α‐SMA, OPN and mechanistic target of rapamycin (mTOR)/p70S6K signalling was detected by Western blot analysis. FA and rapamycin reduced serum levels of total cholesterol, triacylglycerol, LDL, inhibiting oxidative stress and the inflammatory response. Oil red O and H&E staining demonstrated that FA and rapamycin inhibited atherosclerosis. FA and rapamycin treatment inhibited VSMC dedifferentiation in vitro and in vivo, and FA and rapamycin attenuated the mTOR/p70S6K signalling pathway. Our findings suggest that FA attenuates atherosclerosis development and inhibits VSMC dedifferentiation in high‐fat‐fed LDLR−/− mice by reduced lipid levels and inhibiting oxidative stress and the inflammatory response through mTOR/p70S6K signalling pathway.